Isolasi dan Uji Aktivitas Antimikrobia Bakteri Endofit Akar Mangrove Rhizophora mucronata di Kawasan Ekowisata Mangrove Kupang - Alexander Tage; Chatarina Gradict Semiun; Yulita Iryani Mamulak (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Semi-arid mangrove ecosystems harbor significant potential as sources of endophytic bacteria producing adaptive antimicrobial compounds. This study aimed to isolate and evaluate the antimicrobial activity of endophytic bacteria from Rhizophora mucronata prop and lateral roots across three management zones (core, buffer, and utilization) in the Kupang Mangrove Ecotourism Area. Sampling was conducted in March–April 2026, followed by root surface sterilization and isolation on Nutrient Agar. Phenotypic characterization was performed macroscopically, microscopically, and biochemically, while antimicrobial activity was assessed using the Kirby-Bauer disk diffusion method against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922. From 69 initial colonies, 18 pure isolates were obtained, with Bacillus sp. as the dominant genus (44.4%). Notably, Bacillus sp. isolates ZS-04 and ZI-05 exhibited the most potent bioactivity, yielding very strong (>20 mm) inhibition zones against S. aureus and strong (10–20 mm) inhibition against E. coli. One-way ANOVA revealed no significant zonal differences for S. aureus (p = 0.785), whereas a statistically significant zonal effect was observed for E. coli (p = 0.045), particularly between the utilization and buffer zones. These findings confirm that endophytic Bacillus sp. from R. mucronata roots, particularly isolates ZS-04 and ZI-05, produce bioactive compounds with strong, targeted antibacterial activity against Gram-positive pathogens, highlighting semi-arid mangrove endophytes as promising, stress-adapted reservoirs for novel natural antimicrobial agents.